Psychometric testing of the Duke Activity Status Index in patients with heart failure. (1st June 2015) - Fan, Xiuzhen; Lee, Kyoung Suk; Frazier, Susan K; Lennie, Terry A; Moser, Debra K
Abstract: Background: Patients with heart failure (HF) experience difficulty performing activities of daily living. As impaired functional status is adversely associated with outcomes, it is important to accurately evaluate patient functional status. The Duke Activity Status Index (DASI) is a 12-item, self-administered questionnaire to measure functional status. However, its psychometric properties have not been determined in patients with HF. The purpose of this study was to examine the psychometric properties of the DASI in patients with HF. Methods and results: We used data from 297 patients with a diagnosis of HF (age 61±11 years, 31% female) for psychometric testing. Internal consistency reliability of the DASI was high (Cronbach's alpha=0.86). Criterion-related validity was supported by significantly different DASI scores for each New York Heart Association classification. Construct validity was supported by significant correlation of DASI scores with health-related quality of life ( r = −0.64), depressive symptoms ( r = −0.44), and N-terminal B-type natriuretic peptide ( r = −0.14). Conclusion: Our data support the psychometric properties of the DASI as a measure of functional status in patients with HF. This instrument can be used to evaluate functional status and enhance health care provider understanding of functional status related to daily living from the patient perspective.